2020
DOI: 10.3390/jcm9020386
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Dysbiosis of the Gut Microbiome in Renal Transplant Recipients

Abstract: Renal transplantation is life-changing in many aspects. This includes changes to the gut microbiome likely due to exposure to immunosuppressive drugs and antibiotics. As a consequence, renal transplant recipients (RTRs) might suffer from intestinal dysbiosis. We aimed to investigate the gut microbiome of RTRs and compare it with healthy controls and to identify determinants of the gut microbiome of RTRs. Therefore, RTRs and healthy controls participating in the TransplantLines Biobank and Cohort Study (NCT0327… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 37 publications
(53 reference statements)
3
96
0
1
Order By: Relevance
“…Currently, the findings are mostly limited to cross-sectional or longitudinal observational correlation studies on kidney and liver transplantation. Generally, there is a consensus that transplantation induces a trend towards an unbalanced, so-called dysbiotic gut microbiome, which is characterized by a loss of microbial diversity [34][35][36][37][38][39] and an increase in the Proteobacteria phylum. 35,37,39 Gut microbial changes seem to persist over time, with one study detecting dysbiosis up to 6 years after transplantation.…”
Section: G Ut MI Crob Ial Dys B I Os Is In Solid Org An Tr An S Pl mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the findings are mostly limited to cross-sectional or longitudinal observational correlation studies on kidney and liver transplantation. Generally, there is a consensus that transplantation induces a trend towards an unbalanced, so-called dysbiotic gut microbiome, which is characterized by a loss of microbial diversity [34][35][36][37][38][39] and an increase in the Proteobacteria phylum. 35,37,39 Gut microbial changes seem to persist over time, with one study detecting dysbiosis up to 6 years after transplantation.…”
Section: G Ut MI Crob Ial Dys B I Os Is In Solid Org An Tr An S Pl mentioning
confidence: 99%
“…Generally, there is a consensus that transplantation induces a trend towards an unbalanced, so-called dysbiotic gut microbiome, which is characterized by a loss of microbial diversity [34][35][36][37][38][39] and an increase in the Proteobacteria phylum. 35,37,39 Gut microbial changes seem to persist over time, with one study detecting dysbiosis up to 6 years after transplantation. 39 Some studies suggested minor signs of recovery after the immediate post-transplant period, 36,38 but long-term diversity remained decreased.…”
Section: G Ut MI Crob Ial Dys B I Os Is In Solid Org An Tr An S Pl mentioning
confidence: 99%
“…Those needs that are classified as unmet require provision of some ample spaces for the purpose of imagination in relation to leveraging the strength associated with big data, as well as relevant artificial intelligence (AI) to improve the overall status of patients with kidney diseases [25]. In this article, we discuss the big data concepts in nephrology, describe the potential use of AI in nephrology and transplantation, and also encourage researchers and clinicians to submit their invaluable research, including original clinical research studies [26][27][28][29][30], database studies from registries [31][32][33], meta-analyses [34][35][36][37][38][39][40][41][42][43][44], and artificial intelligence research [25,[45][46][47][48] in nephrology and transplantation. Table 1 demonstrates known and commonly used databases that have provided big data in nephrology and transplantation [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Secondary analyses with sex-stratified tertiles of plasma biotin demonstrated that a low plasma biotin was independently associated with an increased risk of mortality. Potential causes for a low plasma biotin may be an insufficient nutrient intake or dysbiosis of the gut microbiota, which recently was demonstrated in KTR, most likely with chronic use of immunosuppressants as an important contributor [13]. Though biotin status has not been quantified in kidney transplants recipients before, it is known that transplant recipients are prone to vitamin deficiencies, including vitamin B6, vitamin K, vitamin C and vitamin B3 [28,56e58].…”
Section: Sex Stratified Tertiles Of Urinary 3-hic Excretionmentioning
confidence: 99%
“…KTR also suffer from dysbiosis, a disruption in the balance of the gut microbiome, in the years following transplantation [13]. Due to the chronic usage of immunosuppressive medications and frequent usage of antibiotics, KTR may also be susceptible to deficiencies of vitamins produced by microbiota, including biotin [14,15].…”
Section: Introductionmentioning
confidence: 99%